The Effect Of Macroeconomic, Institutional And Corruption Variables On FDI In Asean Countries - Nurul Azizah Az Zakiyyah; Firsty Ramadhona Amalia Lubis; Rintan Nuzul Ainy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The majority of ASEAN members are categorized as developing countries. One of the biggest challenges that developing countries face is economic development. To support economic development, substantial funding is required. One source of funding that can be used is investment in the form of Foreign Direct Invest-ment (FDI), which is a solution to overcome the limitations of domestic capital. The purpose of this study is to identify variables that influence foreign investment in the form of FDI in seven ASEAN countries (Singapore, Indonesia, Malaysia, Thailand, Brunei Darussalam, Vietnam, and the Philippines). The factors studied include macro variables consisting of Gross Domestic Product (GDP), Trade Openness and Inflation, institutional variables consisting of Political Stability and Absence of Violence / Terrorism, Government effectiveness, and corruption level variables measured by the Corruption Perceptions Index (CPI). The analysis method used in this research is panel data regression analysis. The results of the analysis with the best model in the form of a fixed effect model show that the variables of GDP, Trade Openness, Government Effectiveness, and Corruption Perception Index have a significant positive effect on FDI in ASEAN countries, the Inflation variable has a significant negative effect, while Political Stability and Absence of Violence of Terrorism have no effect on FDI flows in ASEAN countries. Keywords: Macroeconomic, Institutional, Corruption, FDI, ASEAN ABSTRAK Mayoritas anggota ASEAN dikategorikan sebagai negara berkembang. Salah satu tantangan paling besar yang diwaspadai oleh negara yang sedang berkembang adalah dalam hal pembangunan ekonomi. Untuk mendukung pembangunan ekonomi, diperlukan pendanaan yang substansial. Salah satu sumber pendanaanyang dapat digunakan adalah investasi dalam bentuk Foreign Direct Investment (FDI), yang merupakan solusi untuk mengatasi keterbatasan modal domestik. Tujuan dari penelitian ini adalah untuk mengidentifikasi variabel yang memengaruhi investasi asing dalam bentuk FDI di tujuh negara ASEAN (Singapura, Indonesia, Malaysia, Thailand, Brunei Darussalam, Vietnam, dan Filipina). Faktor-faktor yang diteliti meliputi variable makro yang terdiri dari Produk Domestik Bruto (PDB), Keterbukaan Perdagangan dan Inflasi, variabel kelembagaan yang terdiri dari Political Stability and Absence of Violence/ Terrorism, Government effectiveness, serta variabel tingkat korupsi yang diukur dengan Corruption Perceptions Index (CPI). Metode analisis yang digunakan dalam penelitian ini adalah analisis regresi data panel. Hasil analisis dengan model terbaik berupa fixed effect model menunjukkan bahwa variabel GDP,Trade Openness, Goverment Effectiveness, dan Coruption Perception Index berpengaruh positif signifikan terhadap FDI di negara ASEAN, variabel Inflasi memiliki pengaruh negatif signifikan, sementara Political Stability and Absence Of Violence of Terrorism tidak memiliki pengaruh terhadap aliran FDI pada negara ASEAN